2015
DOI: 10.3906/sag-1409-77
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori cagA, babA2, and dupA genotypes andcorrelation with clinical outcome in Malaysian patients with dyspepsia

Abstract: Background/aim: The severity of disease outcome in dyspepsia has been attributed to Helicobacter pylori virulence genes. The aim of this study was to determine the distribution of H. pylori virulence genes (cagA, babA2, and dupA) and to determine whether or not there arises a significant correlation with clinical dyspepsia outcomes.Materials and methods: H. pylori genotypes cagA, babA2, and dupA were identified by polymerase chain reactions from gastric biopsy samples in 105 H. pylori-positive patients. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Another study in ethnic groups (Indian, Chinese and Malaya) of Malaysia reported that the prevalence of dupA was 22.9% in patients, which was in line with previous data (21.3%) conducted in Malaysia by Schmidt et al[ 41 ] (2009). In the later study, there was no association between dupA and clinical outcome[ 42 ].…”
Section: Discrepancies Of Dupa With Clinical Outcomentioning
confidence: 99%
“…Another study in ethnic groups (Indian, Chinese and Malaya) of Malaysia reported that the prevalence of dupA was 22.9% in patients, which was in line with previous data (21.3%) conducted in Malaysia by Schmidt et al[ 41 ] (2009). In the later study, there was no association between dupA and clinical outcome[ 42 ].…”
Section: Discrepancies Of Dupa With Clinical Outcomentioning
confidence: 99%
“…Esta prevalencia es muy similar a lo encontrado en Tailandia, donde 96,7% de los infectados por el pat贸geno presentan la cepa cagA-positiva, no obstante, y de manera interesante, en este pa铆s la incidencia por c谩ncer g谩strico no supera los 5/100.000 hab 21 . Otros estudios recientes muestran una prevalencia de 69,5%, 77,3% y 87,5%, para las cepas cagA-positivas en poblaciones de Malasia, India y China, respectivamente [22][23][24] . Por su parte, en Am茅rica Latina, se reportan similares resultados para este tipo de cepas, con prevalencias de 62,6%, 71,0% y 85,6%, para M茅xico, Argentina y Brasil, respectivamente [25][26][27] .…”
Section: Discussionunclassified
“…9 The clinical outcomes caused by these bacteria depend on the host's genetic factors, virulence factors in the H. pylori strain, and environmental factors. 10,11 Identification of these bacteria is needed so that treatment can be given as soon as possible. 7 The diagnostic test options available for H. pylori infection are divided into invasive tests that include endoscopy, histology, culture, rapid urease test, and non-invasive tests, such as urea breath test, stool antigen sets, and serologic.…”
Section: Introductionmentioning
confidence: 99%